Galantamine administration reduces reactive astrogliosis and upregulates the anti-oxidant enzyme catalase in rats submitted to neonatal hypoxia ischemia. Issue 62 (November 2017) - Odorcyk, F.K.; Nicola, F.; Duran-Carabali, L.E.; Figueiró, F.; Kolling, J.; Vizuete, A.; Konrath, E.L.; Gonçalves, C.A.; Wyse, A.T.S.; Netto, C.A.
Highlights: Pre-hypoxia galantamine treatment is able to prevent tissue injury. Pre-hypoxia galantamine treatment and increase neuronal survival in a model of HI. Pre-hypoxia galantamine treatment increases the catalase anti-oxidant activity. Pre-hypoxia galantamine treatment reduces astrogliosis 24 h and 38 days after injury. Abstract: Neonatal hypoxia ischemia (HI) plays a role in the etiology of several neurological pathologies and causes severe sequelae. Acetylcholine is a neurotransmitter in the central nervous system and cholinesterase inhibitors have demonstrated a positive action over HI induced deficits. In order to evaluate the effects of pre and post-hypoxia administrations of galantamine, a cholinesterase inhibitor, in a model of perinatal HI, Wistar rats in the post-natal day 7 (PND7) were subjected to a combination of unilateral occlusion of the right carotid artery with the exposure to a 1 h hypoxia. Intraperitoneal injections of galantamine were administered in two different protocols: one pre and other post-hypoxia. The analysis of brain structures volume at PND45 showed that pre-hypoxia galantamine treatment prevented tissue injury to the ipsilesional hippocampus. Also, immunofluorescence showed HI-induced increase in the number of astrocytes that was prevented by pre-hypoxia treatment. Biochemical analysis was performed in the ipsilesional hippocampus at PND8 and revealed that pre-hypoxia galantamine treatment: 1) prevented the neuronal loss induced by HI; 2) reduced the HI-induced hypertrophy of astrocytes; and 3) caused an increase in the activity of the anti-oxidant enzyme catalase. Overall, treatment with galantamine was able to prevent the brain damage, increase the survival of neurons, reduce astrocytic reaction and increase the activity of the anti-oxidant enzyme catalase in rats submitted to neonatal hypoxia ischemia.